1978
DOI: 10.1002/pol.1978.180160801
|View full text |Cite
|
Sign up to set email alerts
|

Small‐angle x‐ray scattering by nylon 6

Abstract: SynopsisSmall-angle x-ray scattering (SAXS) of isotropic or uniaxially oriented nylon 6 was investigated as a function of thermal and mechanical history. In addition to the peak position and linewidth of the SAXS maximum, the integrated SAXS intensity was measured. It was found that the radial intensity distributions of isotropic or arced patterns are controlled to some extent by the small width of the semicrystalline macrolattice, rendering the conventional long period and line shape analysis inapplicable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 47 publications
2
57
1
1
Order By: Relevance
“…Consider, for instance, the rapid decrease in the tensile strength and increase in the shrinkage in PA-6 fibers annealed above 170 8C, and the maximum in the shrinkage stresses at $160 8C (in addition to the one at 90 8C). 78 These are associated with the increases in the density and crystallinity, the increases in the size, orientation, and density of the crystals, and the increases in the long period and the intensity of the corresponding lamellar peak (lamellar intensity). [84][85][86][87][88] However, these changes cannot be quantitatively predicted from the available structural models and the known crystallization behavior.…”
Section: Temperature Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider, for instance, the rapid decrease in the tensile strength and increase in the shrinkage in PA-6 fibers annealed above 170 8C, and the maximum in the shrinkage stresses at $160 8C (in addition to the one at 90 8C). 78 These are associated with the increases in the density and crystallinity, the increases in the size, orientation, and density of the crystals, and the increases in the long period and the intensity of the corresponding lamellar peak (lamellar intensity). [84][85][86][87][88] However, these changes cannot be quantitatively predicted from the available structural models and the known crystallization behavior.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…These changes begin to occur at 160-190 8C in PA-6. 78,85,[87][88][89][90][91] This could be due to crystalline chain relaxation that also accounts for premelting structural transitions, 87 the Brill transition being the most widely known among these. …”
Section: Temperature Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an effect has frequently been found after a drawing of polymer materials. [43][44][45][46][47][48][49] MFC7 is very close to local fiber symmetry. Thus, application of XSF-CT results in almost perfect reconstruction of the nanostructure.…”
Section: Discussionmentioning
confidence: 99%
“…An integration of the transverse layer-line profile provides the total disc intensity and this method has been applied to polymers (Matyi & Crist, 1978). In the present X-ray experiments using pinhole (limited slit) collimation, the X-ray beam contributes noticeably to the broadening of the layerline profiles and it can be shown that knowledge of the correction factor and the size of the X-ray beam is needed before the Fourier-transform values can be obtained (Crist & Worthington, 1980).…”
Section: ~= Db/(2sm)mentioning
confidence: 99%